Paramedics' Newborn Life Support Knowledge and Skills Before and After a Targeted Simulation-Based Educational Intervention - Mileder, Lukas P.; Gressl, Jennifer; Urlesberger, Berndt; Raith, Wolfgang (Frontiers in Pediatrics, 2019)
Objective: Cardiopulmonary resuscitation of neonates after birth in the out-of-hospital environment is challenging. Thus, we aimed to assess paramedics’ newborn life support knowledge and skills before and after targeted simulation-based training. Methods: Voluntary paramedics were recruited from a single Red Cross division. During a one-day simulation-based educational intervention, essential aspects of neonatal resuscitation were taught and practiced. Before and after practical training, we assessed 1) knowledge of current European Resuscitation Council (ERC) guidelines using a 20-item-questionnaire and 2) the quality of simulated bag-valve-mask ventilation by means of mask leakage, measured by a respiratory function monitor (SMART Newborn Resuscitation Training System, GM Instruments Ltd., Great Britain). Data are presented as median (minimum/maximum or interquartile range [IQR]). Analyses were performed using IBM® SPSS Statistics 22 with a significance level of p<0.05. Results: Forty-one paramedics participated in the initial survey and 12 took part in the simulation-based educational intervention. There was a significant increase in the number of correctly answered questions: 62.1% (IQR 37.5%-77.4%) versus 91.7% (IQR 83.3%-100%; p=0.001). A total of 1332 ventilations were analyzed. The proportion of substantial mask leakage >75% decreased significantly after training (15.8% versus 6.1%; p<0.001), while median mask leakage was similar (17.0% [IQR 0.0-55.0%] versus 18.0% [IQR 6.0-34.0%]; p=0.414). Conclusions: Theoretical knowledge of current ERC guidelines among paramedics was moderate in this study. Participation in a targeted simulation-based educational intervention led to a significant increase in theoretical knowledge. The initially already high quality of simulated ventilation was further increased after simulation-based training using respiratory function monitoring.